2009
DOI: 10.1074/jbc.m109.016501
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Endothelial Cells by Tissue-invasive M3 Type Group A Streptococci Requires Src Kinase and Activation of Rac1 by a Phosphatidylinositol 3-Kinase-independent Mechanism

Abstract: Streptococcus pyogenes can cause invasive diseases in humans, such as sepsis or necrotizing fasciitis. Among the various M serotypes of group A streptococci (GAS), M3 GAS lacks the major epithelial invasins SfbI/PrtF1 and M1 protein but has a high potential to cause invasive disease. We examined the uptake of M3 GAS into human endothelial cells and identified host signaling factors required to initiate streptococcal uptake. Bacterial uptake is accompanied by local F-actin accumulation and formation of membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Several reports have shown that serotype M1 S. pyogenes efficiently invades and survives within various cell types including phagocytic and non-phagocytic cells [4,5,6,8,10,12,19,26]. In this study, we provide evidence that serotype M1 streptococci efficiently invade human blood EC and that the M1 protein is a key molecule in this process.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Several reports have shown that serotype M1 S. pyogenes efficiently invades and survives within various cell types including phagocytic and non-phagocytic cells [4,5,6,8,10,12,19,26]. In this study, we provide evidence that serotype M1 streptococci efficiently invade human blood EC and that the M1 protein is a key molecule in this process.…”
Section: Discussionsupporting
confidence: 51%
“…Although the invasion factors of M3 and M1 S. pyogenes are distinct, both trigger similar uptake processes with phago-lysosomal destination (fig. 2) [19,20]. However, there are also other important factors that may have a strong impact on the EC invasion by GAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that several intracellular pathogens utilize Src kinase for internalization and dissemination (16,32,51,61,78,90), we tested whether specific Src family kinase (SFK) inhibitors inhibited B. burgdorferi internalization in vitro. Specifically, Src kinase activity is required for the internalization of Neisseria spp.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion and migration of tumor is a multi-procedure and multistage process including shedding from of tumors from primary focus of infection, degradation of extracellular matrix (ECM), invasion into the blood vessel or absorbent vessel, transferring through the circulation system, escaping from the blood vessel or absorbent vessel, and formation of fresh focus of infection through proliferation and angiogenesis. This process requires complex molecular mechanisms including the participation of multiple cytokines, growth factors, adhesion factors and proteases (Lash et al, 2006;Mihaljevic et al, 2010;Nerlich et al, 2009;Wong and Gumbinger, 2003). Through wide-scale screening for CTCF binding site by CHIP, CTCF might also regulate the expression of proteins similar to cadherin like 26 and MMP23B (Arpanahi et al, 2009;Mukhopadhyay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%